The combination of Slow Deep Breathing (SDB) and Progressive Muscle Relaxation (PMR) to reduce blood pressure in hypertension patients: A case study - Achmad Fikri Zakaria Ar-Razy; Anis Ika Nur Rohmah (School of Health Sciences Al-Ma'arif, 2025)
Background: Hypertension is a major global health problem and one of the leading causes of death worldwide. Known as a silent killer, hypertension often shows no clear symptoms but can cause serious complications if not properly managed. Non-pharmacological relaxation techniques such as Slow Deep Breathing and Progressive Muscle Relaxation are effective in lowering blood pressure by reducing stress and muscle tension. Objective: This study aimed to determine the effectiveness of the combination of Slow Deep Breathing and Progressive Muscle Relaxation therapy in reducing blood pressure among hypertensive patients. Methods: This research used an indicative case study approach involving one 48-year-old respondent with hypertension living in Sukoanyar Village, Pakis District, Malang Regency. Inclusion criteria included participants aged 30–60 years, diagnosed with hypertension, without respiratory disorders or physical limitations. Exclusion criteria included participants with physical abnormalities that interfered with the exercise intervention or inability to perform relaxation and breathing exercises. The intervention was conducted once daily for approximately 15 minutes over five consecutive days. Blood pressure was measured before and after the intervention. Results: There was a gradual decrease in blood pressure from the first to the fifth day, with an initial measurement of 178/105 mmHg decreasing to 158/87 mmHg after five days of intervention. Conclusion: The combination therapy of Slow Deep Breathing and Progressive Muscle Relaxation was proven effective in reducing blood pressure in hypertensive patients. This intervention is simple, safe, and can be performed independently at home to support blood pressure control. However, due to the short duration of intervention, the results are indicative and do not reflect the long-term therapeutic effect.